A complex protein derivative acts as biogenic elicitor of grapevine resistance against powdery mildew under field conditions - Nesler, Andrea; Perazzolli, Michele; Puopolo, Gerardo; Giovannini, Oscar; Elad, Yigal; Pertot, Ilaria (Frontiers in Plant Science, 2015)
Powdery mildew caused by Erysiphe necator is one of the most important grapevine diseases in several viticulture areas, and high fungicide input is required to control it. However, numerous synthetic chemical pesticides are under scrutiny due to concerns about their impact on human health and the environment. Biopesticides, such as biogenic elicitors, are a promising alternative to chemical fungicides. Although several studies have reported on effective elicitors against grapevine diseases, their efficacy under field conditions has not been investigated extensively or has occurred at rather limited levels. Our goal was to examine the efficacy of a protein-based composition, namely nutrient broth (NB), against powdery mildew under field conditions and to characterize its mechanism of action. Weekly treatments with NB was highly effective in controlling powdery mildew on grapevine across seasons with different disease pressures. The level of disease control achieved with NB was comparable to standard fungicide treatments both on leaves and bunches across three different years. NB has no direct toxic effect on the germination of E. necator conidia, and it activates plant resistance with both systemic and translaminar effect in experiments with artificial inoculation under controlled conditions. NB induced the expression of defense-related genes in grapevine, demonstrating stimulation of plant defense mechanisms, prior to and in the early stages of pathogen infection. NB is a natural derivative from meat and yeast, substances that tend not to raise concerns about toxicological and ecotoxicological properties. NB represents a valid control tool for integrated plant protection programs against powdery mildew, to reduce the use of synthetic pesticides on grapevine.